Modulation of instrumental responding by a conditioned threat stimulus requires lateral and central amygdala - Campese, Vincent D.; Gonzaga, Rosemary; Moscarello, Justin M.; LeDoux, Joseph E. (Frontiers in Behavioral Neuroscience, 2015)
Two studies explored the role of the amygdala in response modulation by an aversive conditioned stimulus (CS) in rats. Experiment 1 investigated the role of amygdala circuitry in conditioned suppression using a paradigm in which licking for sucrose was inhibited by a tone CS that had been previously paired with footshock. Electrolytic lesions of the lateral amygdala impaired suppression relative to sham-operated animals, and produced the same pattern of results when applied to central amygdala. In addition, disconnection of the lateral and central amygdala, by unilateral lesion of each on opposite sides of the brain, also impaired suppression relative to control subjects that received lesions of both areas on the same side. In each case, lesions were placed following Pavlovian conditioning and instrumental training, but before testing. This procedure produced within-subjects measures of the effects of lesion on freezing and between-group comparisons for the effects on suppression. Experiment 2 extended this analysis to a task where an aversive CS suppressed shuttling responses that had been previously food reinforced and also found effects of bilateral lesions of the central amygdala in a pre-post design. Together, these studies demonstrate that connections between the lateral and central amygdala constitute a serial circuit involved in processing aversive Pavlovian stimuli, and add to a growing body of findings implicating central amygdala in the modulation of instrumental behavior.